The Impact of Translation Techniques on The Translation Quality in The White Lady’s Subtitle - Putri, Devanni Kusuma (Universitas Sebelas Maret, 2022)
This study aimed to find out the impact of the translation techniques used by the translator in The White Lady’s subtitles of Pamali: Indonesian Folklore Horror Game. This study applied descriptive qualitative method. The data in this study were obtained through document analysis and Focus Group Discussion (FGD). The theory of translation techniques used for analysing the technique in this study was proposed by Molina and Albir (2002). This research also assessed the translation quality by using the model of Translation Quality Assessment proposed by Nababan, et al (2012). The translation quality and the assessment were done through FGD with three raters. The result showed that there were 18 techniques applied in the subtitle. This study found that established equivalent affected the translation quality in positive way. Meanwhile, deletion technique gave the bad impact on all aspects of translation quality. This study also discovered the technique namely variant borrowing that was found by Dyah (2019). The average score of accuracy, acceptability, and readability respectively was 2,94, 2,96, and 2,97. Therefore, the score of the translation quality was high with 2.95 of 3.